Memahami Lebih Dalam Mengenai Pentingnya Pencegahan Penularan Covid-19 Sejak Usia Dini di TPQ Al-Mubarok - Rohman Hariri, fajar (JRCE (Journal of Research on Community Engagement), 2021)
It takes an intensive understanding of the corona virus and how to deal with it so that the spread rate does not increase. Especially early childhood, including those who are vulnerable to the Covid-19 virus because they do not understand how fast this virus spreads and still have an immune system that is vulnerable to the virus. With the Covid-19 virus, it has resulted in children being unable to study at school, so learning activities must also be supported by parents at home and teachers are also responsible for monitoring children's learning activities. This Covid-19 virus also brings fear and worry to children, this is because children do not understand how they understand the virus and how to prevent it. Therefore, it is very important to carry out socialization or education about the prevention of Covid-19 for children -child. Covid-19 prevention education contains the introduction of the Covid-19 virus, how to deal with worry, and how to prevent the Covid-19 virus through short animated videos that are interesting and easy for children to understand, so that children's worries can be reduced and parents will also understand how to teach children to prevent the virus.